Translations of Ukrainian Poetry. Translation of Bohdan Stupka's and Lina Kostenko's Poetry into Spanish (PROBLEMS OF SEMANTICS, PRAGMATICS AND COGNITIVE LINGUISTICS, 2024)
Tarasenko Yu. Translation of Bohdan Stupka's and Lina Kostenko's Poetry into Spanish